The expression
is evaluated using the given functions' graphs. Substituting the corresponding values yields
![\(f(-4) - 3 \cdot g(-2) = -12\).](https://img.qammunity.org/2022/formulas/mathematics/high-school/nznxbsak7l87y6lb38ccbhnb7n07bgleag.png)
To find f(−4)−3⋅g(−2), we look at the given values in the functions' graphs. For f(−4), we find that the corresponding y-value is -3. For g(−2), the corresponding y-value is 3. Substituting these values into the expression:
![\[ f(-4)-3.g(-2) = (-3) - 3 \cdot 3 = -3 - 9 = -12 \]](https://img.qammunity.org/2022/formulas/mathematics/high-school/9adrl2zdh39n72ltbtm96983efzl3vof3v.png)
Therefore, f(−4)−3⋅g(−2) = -12. The graph values indicate that at x = -4 in function f, the y-value is -3, and at x = -2 in function g, the y-value is 3. Subtracting three times the g value from the f value gives -12.